Improved thermal stability of ferro/piezo-electric properties of Mn-doped Pb(In1/2Nb1/2)O3-PbTiO3 ceramics. Issue 9 (August 2018) - Qiao, Huimin; He, Chao; Wang, Zujian; Li, Xiuzhi; Liu, Ying; Long, Xifa
Abstract: Thermal stability of piezo-/ferro-electric properties of ferroelectrics is important for the devices working at elevated temperature. A study on thermal stability of ferroelectrics will be greatly helpful for future applications. In this work, thermal behaviors of electrical properties were studied in Mn-doped Pb(In1/2 Nb1/2 )O3 -PbTiO3 (PINT) ceramics. The ferroelectric hysteresis loops of Mn-doped samples change anomalously with increasing temperature compared with the virgin sample. Remnant polarization of PINT ceramics with high manganese content ( x  ≥ 0.04) exhibits increase trend as temperature increasing, leading to a negative electrocaloric effect which was reported to be beneficial to improving the cooling efficiency. For Mn-doped PINT ceramics, the reduction rate of coercive field reaches a relatively low value of 3%, indicating outstanding ability of depolarization resistance. PINT ceramics with proper dopant concentration show improved aging resistance and thermal stability of piezoelectric property after annealed. Out-of-plane domain configurations show different features at room temperature and elevated temperatures.